Under the mantra: ‘Make use of colorblind friendly graphs’ - Rocchini, Duccio; Chieffallo, Ludovico; Thouverai, Elisa; D'Introno, Rossella; Dagostin, Francesca; Donini, Emma; Foody, Giles; Garnier, Simon; Mazzochini, Guilherme G.; Moudry, Vitezslav; Rudis, Bob; Simova, Petra; et al. (Environmetrics (London, Ont.), 2024)
Colorblindness is a genetic condition that affects a person's ability to accurately perceive colors. Several papers still exist making use of rainbow colors palette to show output. In such cases, for colorblind people such graphs are meaningless. In this paper, we propose good practices and coding solutions developed in the R Free and Open Source Software to (i) simulate colorblindness, (ii) develop colorblind friendly color palettes and (iii) provide the tools for converting a noncolorblind friendly graph into a new image with improved colors.